2015
DOI: 10.1002/cphc.201500906
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐Confined Supramolecular Self‐Assembly of Molecular Nanocranes for Chemically Lifting and Positioning C60 above a Conducting Substrate

Abstract: 2D supramolecular self-assembly is a good way to form well-defined nanostructures on various substrates. One of the current challenges is to extend this approach to 3D functional building blocks. Here, we address this issue by providing a strategy for the controlled lifting and positioning of functional units above a graphitic substrate. This is the first time that multistory cyclophane-based 3D tectons incorporating C60 units have been designed and synthesized. Molecular modelling provides a description of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Du et al took advantage of the cyclophane chemistry to build a multi-story pillar that allows the tuning of the distance between the functional unit and the substrate. 43 This highly versatile approach allows through the modification of the upper-face, for the preparation of a wide range of 3D Janus tectons that expose various functional units ranging from fluorophores to functional moieties for potential uses, such as for hydrogen-bonding, metal-ligand bonding, and redox processes. 44 The effectiveness of the electronic decoupling will be evidenced in part 3.d.…”
mentioning
confidence: 99%
“…Du et al took advantage of the cyclophane chemistry to build a multi-story pillar that allows the tuning of the distance between the functional unit and the substrate. 43 This highly versatile approach allows through the modification of the upper-face, for the preparation of a wide range of 3D Janus tectons that expose various functional units ranging from fluorophores to functional moieties for potential uses, such as for hydrogen-bonding, metal-ligand bonding, and redox processes. 44 The effectiveness of the electronic decoupling will be evidenced in part 3.d.…”
mentioning
confidence: 99%
“…However, STM is not suitable for imaging such movable features. Du et al [7] reported the first example of robust fullerene nanoarchitectures covalently templated by the underlying Janus tecton SAMs. The authors found that the flexibility of the fullerenes poses a major challenge for STM imaging.…”
Section: Perspectivementioning
confidence: 99%
“…Moreover, in this case the POMs should be deposited on the backbone of the supramolecular network and not in the pores, restricting direct interaction with the substrate, thereby avoiding pore-filling schemes that might require supplementary synthesis steps. [38][39][40] To prove unambiguously the homogeneous and periodic organization of the POMs, various characterizations were performed at different scales. Macroscale deposition of the POMs directed by electrostatic interactions on the protonated triazine core was first confirmed by X-ray photoemission spectroscopy (XPS).…”
mentioning
confidence: 99%